Milk proteins : from expression to food - Thompson, Abby; Boland, Mike, 1950-; Singh, Harjinder, 1957- (Academic Press, 2014)
Understanding of the interactions of milk proteins in complex food systems continues to progress, resulting in specialized milk-protein based applications in functional foods, and in protein ingredients for specific health applications. Milk Proteins is the first and only presentation of the entire dairy food chain - from the source to the nutritional aspects affecting the consumer. With focus on the molecular structures and interactions of milk proteins in various processing methods, Milk Proteins presents a comprehensive overview of the biology and chemistry of milk, as well as featuring the latest science and developments. Significant insight into the use of milk proteins from an industry viewpoint provides valuable application-based information. Those working with food and nutritional research and product development will find this book useful.
Keywords: bílkoviny; nutraceutika; zpracování mléka; mléčné výrobky; proteins; nutraceuticals; dairy products; dairy processing; mléčné proteiny; elektronické knihy; electronic books